Impact and GNSS-based deformation analysis of the earthquake in Türkiye on 6 February, 2023: a case study of the TAG (Tarsus–Adana–Gaziantep) motorway and Hatay airport - Aslan, Hakan; Kocaman, Hakan; Sıkar, Recep Bilal; Turan, İbrahim Can (Frontiers in Built Environment, 2025)
Transportation structures that provide rescue, first aid, and emergency services after an earthquake are critical for ensuring mobility within affected regions. The Tarsus–Adana–Gaziantep (TAG) motorway, passing through the Gaziantep Nurdağı district, is one of the most important transportation arteries in the earthquake-affected region. This study aims to assess the earthquake performance of transportation infrastructures along the TAG motorway, which is under the authority of the 5th Regional Directorate of the General Directorate of Highways (KGM). In this study, transportation structures such as viaducts, underpasses, overpasses, road retainers, drainage systems, and traffic safety elements along the TAG motorway were inspected and documented through on-site photography. The coordinates of these structures were determined using Global Navigation Satellite Systems (GNSS). The collected data was integrated with earthquake data from the Ministry of Internal Affairs Disaster and Emergency Management Presidency (AFAD) and analyzed using Geographic Information System (GIS) software. The inspection of the TAG motorway revealed that it is a vital transportation route connecting airports, state roads, and urban networks. Significant deformations were observed in the transportation structures, especially in the province of Hatay, where the road leading to the city’s airport was notably affected by the earthquake. Furthermore, the study also evaluated the impact on the transportation networks and traffic characteristics of Gaziantep and Hatay provinces. The findings highlight the vulnerability of transportation infrastructures in earthquake-prone areas and the importance of assessing and reinforcing these structures to ensure functionality during future seismic events. The study provides valuable data that can be used to improve the design and reinforcement strategies for transportation structures to withstand earthquakes.